2015
DOI: 10.1093/jxb/erv529
|View full text |Cite
|
Sign up to set email alerts
|

PGL, encoding chlorophyllide a oxygenase 1, impacts leaf senescence and indirectly affects grain yield and quality in rice

Abstract: Highlight PGL encodes CAO1 in rice, which is essential for Chl b synthesis and affects Chl synthesis and degradation. PGL also impacts leaf senescence and indirectly affects grain yield and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 51 publications
3
98
0
Order By: Relevance
“…The chlorophyll content was determined according to the method previously described (Yang et al, 2016). Net photosynthesis rate was measured using a Walz GFS-3000 (Eichenring).…”
Section: Chlorophyll Content and Net Photosynthesis Ratementioning
confidence: 99%
“…The chlorophyll content was determined according to the method previously described (Yang et al, 2016). Net photosynthesis rate was measured using a Walz GFS-3000 (Eichenring).…”
Section: Chlorophyll Content and Net Photosynthesis Ratementioning
confidence: 99%
“…Mutations to any of these genes may reduce or even eliminate chlorophyll biosynthesis, leading to leaf color changes (Liu et al, 2007, 2016; Yoo et al, 2009; Tian et al, 2013; Wang et al, 2014; Zhang et al, 2015; Yang et al, 2016). Through gene mapping and additional studies, the mutant gene responsible for the xantha marker trait of HYB was identified as a mutated OsGUN4 ( genomes uncoupled 4 ) (Chi et al, 2010; Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They were soaked in 2.5 mg ml −1 trypan blue solution at room temperature for 1 hr and then decolored by soaking in lactophenol/ethanol solution. ROS level in the leaves was detected by nitro blue tetrazolium (NBT) and diamino benzidine (DAB) staining as previously described (Yang et al, ; Wang, He, et al, ).…”
Section: Methodsmentioning
confidence: 99%